Hubungan Kepercayaan Diri dalam Pembelajaran Matematika dengan Hasil Belajar Matematika Siswa - Mikhael R. V. Lioso; Derel F. Kaunang; Regina N. Pakpahan (Journal on Education, 2023)
Mikhael Rian Vernando Lioso. 22504061.. The Relationship of Self-Confidence in Learning Mathematics with Students' Mathematics Learning Outcomes. Department of Mathematics. FMIPA. UNIMA. 2023. This study aims to determine the relationship between self-confidence and students' mathematics learning outcomes. This research uses a quantitative approach with a correlational survey method. The subjects of this study were all VIII grade students of SMP Negeri 4 Suluun Tareran in the 2023/2024 school year with a population of 40 students and a sample of 37 students. Self-confidence data is obtained from a questionnaire distributed to students, while learning outcomes data is obtained through documentation of odd semester midterm exam results in the 2023/2024 school year. The data analysis technique uses a simple correlation technique, with α = 0.05. as for the results of the research obtained is that there is a positive relationship between self-confidence and student mathematics learning outcomes by 29.7%, which means significant